2007
DOI: 10.1111/j.1463-1318.2007.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Faecal incontinence in male patients

Abstract: Prostate cancer, symptomatic haemorrhoids, perianal sepsis, rectal cancer and a history of restorative rectal resection were common associations with FI in men. The aetiologies for FI in men vary with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 73 publications
3
19
0
2
Order By: Relevance
“…In women, the cause of sphincter trauma is most commonly obstetric, with 23% to 45% of primigravidas having sonographic evidence of sphincter damage following delivery, 18 whereas in men who have sphincter injury, the damage appears primarily iatrogenic. 4,8 Alternative pathoetiologic factors for the development of FI in men must therefore be considered. This study shows that the majority of men with FI report coexistent symptoms of constipation and rectal evacuatory dysfunction (RED), confirmed in a proportion on evacuation proctography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In women, the cause of sphincter trauma is most commonly obstetric, with 23% to 45% of primigravidas having sonographic evidence of sphincter damage following delivery, 18 whereas in men who have sphincter injury, the damage appears primarily iatrogenic. 4,8 Alternative pathoetiologic factors for the development of FI in men must therefore be considered. This study shows that the majority of men with FI report coexistent symptoms of constipation and rectal evacuatory dysfunction (RED), confirmed in a proportion on evacuation proctography.…”
Section: Discussionmentioning
confidence: 99%
“…7 Understanding the etiologic mechanisms other than traumatic childbirth is therefore fundamental in men, in whom information concerning cause is less well established. Recently, studies 4,8 have shown that the majority of men with FI have a past history of perianal disease (including hemorrhoids and perianal sepsis), with 58% having a history of at least one surgical procedure. However, it has also been reported that up to 40% of men have no structural abnormalities on endoanal ultrasound to explain symptoms.…”
mentioning
confidence: 99%
“…Wexner and colleagues recently reported a large cohort of males with FI [16]. Males represented 29% of their incontinent patients.…”
Section: Male Incontinencementioning
confidence: 95%
“…Prostate cancer, symptomatic haemorrhoids, perianal sepsis, rectal cancer and proctectomy/proctocolectomy with appropriate reconstructive surgery were associated conditions in patients of all ages. In younger patients, perineal injury, perianal sepsis, imperforate anus and anal cancer were significantly more common, whereas urological and neurological diseases were significantly more common in older patients [16].…”
Section: Male Incontinencementioning
confidence: 99%
“…The effect of rectal cancer surgery is often to reduce the rectal capacity, which, combined with radiotherapy, commonly reduces the ability to defer defaecation 37 . Indeed, the incidence of faecal incontinence following pelvic radiotherapy alone has been reported to be as high as 58% 38 …”
Section: Management Of Synchronous Prostate and Rectal Cancermentioning
confidence: 99%